Public Service Management in Corporate Social Responsibility PT. Pertamina International Refinery Unit II Sungai Pakning - Dadang Mashur; Zaili Rusli; Zulkarnaini Zulkarnaini; Abdul Sadad; Geovani Meiwanda (Universitas Padjadjaran, 2024)
Environmental matter frequently emerges in every area; this is a concern for all parties, especially as environmental problems are the impact of company activities. As a company responsible for the impact of activities carried out, the company provides public services in the form of a corporate social responsibility program. Good public service management in corporate social responsibility programs certainly has a positive social impact on society and the environment. This has been conducted by PT. Pertamina International Refinery Unit II Sungai Pakning received five best performance awards from the Ministry of Environment and Forestry of the Republic of Indonesia in a row from 2017. The purpose of this research is to analyze public service management in corporate social responsibility. This research uses a qualitative research method with a phenomenological approach. The research results found that there are four stages in public service management in corporate social responsibility, namely planning, implementation, reporting, and accountability. This stage is the basis for implementing corporate social responsibility programs that focus on the fields of education, public health, environment, and infrastructure. It was found that there was an additional general function in the company's CSR public service management, namely accountability.